Answer:
18
Step-by-step explanation:
don't step answer. Because I am lol
Answer:
2
Step-by-step explanation:
cause 20 percent of 10 is 2 lol
B. y = -3(x + 3)2 - 6
C. y = -3(x - 3)2 + 6
D. y = -3(x - 3)2 - 6
Answer:
Step-by-step explanation:
=========================================================
How to get this answer:
Locate 6 on the x axis. Draw an arrow down until you reach the f(x) curve, then move to the left until you reach the y axis. We started at x = 6 and ended on y = -6. See the diagram below for this process in action.
So basically f(6) = -6. Visually the point (6,-6) is on the f(x) curve.
Through similar steps, we see that g(5) = -5
Therefore,
4*f(6) - 6*g(5) = 4*(-6) - 6*(-5) = -24 + 30 = 6
Answer:
the value increased by0.0388
Step-by-step explanation
4% - 3% equals 0.0388 becuase its the diffrence between them is 0.0388